SAT0134 Prevalence of Cardiovascular Risk Factors and Cardiovascular Disease in Rheumatoid Arthritis Patients across International Regions: A Comparison of the Corrona International and Corrona US Registries. (10th June 2014) - Pappas, D.A.; Lampl, K.; Kremer, J.M.; Radominski, S.C.; Gal, J.; Nyberg, F.; Malaviya, A.; Whitworth, A.; Rillo, O.L.; Gibofsky, A.; Popkova, T.V.; Ho, M.; et al.
Abstract : Background: Cardiovascular disease (CVD) is a major comorbidity in patients (pts) with rheumatoid arthritis (RA). We explored variations in the prevalence of cardiovascular (CV) risk factors and CVD among RA pts in different international regions using data from CORRONA International (C.Intl) and CORRONA US (C.USA) RA registries. Methods: The C.Intl registry is a multi-center, observational registry. Adult RA pts have been enrolled from 83 rheumatology practices in 10 countries in 3 regions - Latin America (Mexico, Brazil, Argentina), Eastern Europe (Poland, Czech Republic, Hungary, Romania, Russia, Ukraine), Asia (India). The C.USA registry enrolls pts from 111 rheumatology practices across the United States. Both registries collect data in a similar manner from rheumatologists and RA pts at regular clinical encounters. We compared cross-sectional baseline descriptive C.Intl data for demographic and disease characteristics with cross-sectional data from the most recent visit of C.USA-enrolled pts. Prevalence for CV risk factors and CVD are presented crude for C.USA and age/gender-standardized to the C.USA age/gender distribution (age categories <50, 50-<60, 60-<70, ≥70 years) for C.Intl regions. Results: We analyzed 5696 pts enrolled in C.Intl and 20291 pts actively followed in C.USA. While there are cross-sectional differences across all regions, the greatest differences are between the US and C.Intl regions overall. There is a higher percentage of male pts in C.USA, disease duration is longer, and pts tend to have lower disease activity, yet are more likely to receive a biologic (Table 1 ). After adjusting for age and gender differences by standardization, enrolled pts in India have the lowest BMI, are more rarely smokers and have a low prevalence of hyperlipidemia and CVD compared to other C.Intl regions and C.USA (Table 1 ). C.USA participants have the highest BMI. Participants from Eastern Europe suffer more frequently from hypertension and hyperlipidemia and have the highest prevalence of all manifestations of CVD (Table 1 ). Conclusions: Data from the C.Intl and C.USA registries reveal variations in disease characteristics, as well as prevalence of CV risk factors and CVD, across different regions. Observed variations may be influenced by differences in the composition and treatment of pts populations, and this should be considered in analyses and evaluation of pts from different geographic origins. Acknowledgements: This study is sponsored by CORRONA. Initial funding for the CORRONA International was provided by AstraZeneca. In the last two years, AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Lilly, Novartis, Pfizer, Savient, Vertex, and UCB have supported CORRONA through contracted subscriptions. Disclosure of Interest: D. Pappas Employee of: CORRONA, Inc., Paid instructor for: Novartis, K. Lampl Shareholder of: AstraZeneca, Employee of: AstraZeneca, J. Kremer Shareholder of: CORRONA, Inc., Employee of: CORRONA, Inc., S. Radominski Consultant for: Pfizer, BMS, AstraZeneca, Employee of: Universidade Federal do Parana- Curitiba- Brazil;, Speakers bureau: Pfizer, BMS, AstraZeneca, Janssen, Sanofi, GSK, J. Gal: None declared, F. Nyberg Shareholder of: AstraZeneca, Employee of: AstraZeneca, A. Malaviya Consultant for: Part-time Consultant Rheumatologist at ISIC Hospital, Advisory Board Member Janssen Pharma, Roche Pharma, Pfizer Pharma, Sanofi Pharma, A. Whitworth Employee of: CORRONA, Inc., O. Rillo: None declared, A. Gibofsky Shareholder of: Amgen, BMS, GlaxoSmithKline, Johnson&Johnson, Pfizer, Roche, Consultant for: Amgen, AstraZeneca, Celgene, Horizon, Iroko, Pfizer, Roche, Antares, UCB, Speakers bureau: Amgen, Pfizer, Roche, UCB, T. Popkova Speakers bureau: GlaxoSmithKline, MSD, AstraZeneca, M. Ho Employee of: AstraZeneca, I. Laurindo Consultant for: Abbott, AstraZeneca, Bristol, Janssen, Pfizer, Speakers bureau: Abbott, AstraZeneca, Bristol, Janssen, Pfizer, Roche, G. Reed Employee of: CORRONA, Inc., E. Kerzberg: None declared, L. Horne Shareholder of: AstraZeneca, Employee of: AstraZeneca, R. Zahora: None declared, K. Saunders Employee of: CORRONA, Inc., B. Pons-Estel Grant/research support: GLADAR, Abbott Laboratories, A. Onofrei Employee of: UMASS Medical School, J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca, Pfizer, Employee of: CORRONA, Inc. DOI: 10.1136/annrheumdis-2014-eular.1695